In-vitro and in-vivo bio-corrosion and biocompatibility responses of bioactive TiTaNb films with various Ta contents on Ti6Al4V implants - Y.H. Chen; W.Y. Chen; Y.S. Lin; C.H. Chen; Rui Zhou; T.H. Chou; W.P. Li; X. Wang; S.C. Chen; C.Y. Chen; Y.T. Zhu; J.C. Huang (Journal of Materials Research and Technology, 2023)
Despite the widespread use of Ti6Al4V in orthopedics, the health concerns, innate bio-inert property and the pursuit of long-term implantation in the body limit its development. For these reasons, we intend to modify the chemical and physical properties of Ti6Al4V by the sputtered bioactive Ti–Ta–Nb films. All these elements exhibit great biocompatibility in human body and the Ti–Ta–Nb system can form more stable passive layer to prevent the corrosion. In this study, we evaluate the effectiveness of the surface modification for Ti–Ta–Nb system on Ti6Al4V and investigate the influence of bioactive element Ta content from 25, 33, to 50 at% by the bio-corrosion behavior, passivation, in-vitro biological analysis and in-vivo implantation. The results show the Ti–Ta–Nb system has higher corrosion resistance and better biological properties than Ti6Al4V. Furthermore, following the electrochemical tests and passive layer observation, with increasing Ta content in Ti–Ta–Nb system, the corrosion resistance increases. The in-vitro measurements demonstrate that the higher Ta content in this system would lead to favorable surface condition for cell viability, proliferation, differentiation and adhesion. As for the in-vivo response upon implantation, the Ta50 film demonstrates significantly greater osteointegration capability. In summary, the current results reveal that the Ti–Ta–Nb system could greatly promote the surface properties of Ti6Al4V, and Ta50 is demonstrated to be a more promising coating choice for orthopedic implants. The mechanisms of the influence on Ta via the corrosion resistance, passivation and biological performances have been extensively explored and discussed.